2003
DOI: 10.1093/soceco/1.1.71
|View full text |Cite
|
Sign up to set email alerts
|

Social movements, field frames and industry emergence: a cultural-political perspective on US recycling

Abstract: This article examines how social movements contribute to institutional change and the creation of new industries. We build on current efforts to bridge institutional and social movement perspectives in sociology and develop the concept of field frame to study how industries are shaped by social structures of meanings and resources that underpin and stabilize practices and social organization. Drawing on the case of how non-profit recyclers and the recycling social movement enabled the rise of a for-profit recy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
506
1
14

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 673 publications
(530 citation statements)
references
References 93 publications
9
506
1
14
Order By: Relevance
“…Our findings are in line with earlier studies (Lounsbury, Ventresca, & Hirsch, 2003;Ritvala & Salmi, 2010) showing that successful mobilization of firms to issue networks is contingent upon the manner that the issue is framed by the network mobilizers. We found that if the issue and its possible solutions were framed in an interesting but loose manner, firms responded positively, because they could incorporate the issue into their strategies and control needed resource commitments.…”
Section: Acting On the Issue Framingsupporting
confidence: 92%
“…Our findings are in line with earlier studies (Lounsbury, Ventresca, & Hirsch, 2003;Ritvala & Salmi, 2010) showing that successful mobilization of firms to issue networks is contingent upon the manner that the issue is framed by the network mobilizers. We found that if the issue and its possible solutions were framed in an interesting but loose manner, firms responded positively, because they could incorporate the issue into their strategies and control needed resource commitments.…”
Section: Acting On the Issue Framingsupporting
confidence: 92%
“…Relevant to our theorizing, studies have linked certain role identities to both social welfare and commercial logics. While not an exhaustive list, clergy (Tracey, 2012), community organizer (Lounsbury, Ventresca, & Hirsch, 2003), parent , social worker, and teacher (Battilana & Dorado, 2010) have been tied to the social welfare logic. Accountant, corporate lawyer (Battilana & Dorado, 2010), manager (Glynn, 2000), and venture capitalist (Wry et al, 2014) role identities, on the other hand, align with commercial logic.…”
Section: The Influence Of Multiple Identities In Venture Creationmentioning
confidence: 99%
“…Theorists have used social movement concepts to describe how mobilization occurs in organizational fields and inside organizations (e.g., Rao, Morrill, and Zald 2000;Lounsbury, Ventresca, and Hirsch 2003;Davis et al 2005;McAdam and Scott 2005;Briscoe and Safford 2008;Davis et al 2008) and inside organizations (e.g., Zald and Berger 1978;Lounsbury 2001;Scully and Creed 2005;Kaplan 2008;O'Mahony and Bechky 2008). These scholars have argued that mobilization may look different inside organizations because of the important role played by top managers (Scully and Segal 2002;Raeburn 2004;Clemens 2005;Zald, Morrill, and Rao 2005;Weber, Thomas, and Rao 2009).…”
Section: Relational Spaces and The Importance Of Inclusionmentioning
confidence: 99%